DEVELOPING AND TESTING OF NON-ASBESTOS FRICTION MATERIALS IN BRAKE MECHANISMS OF THE CRANES AT THE OJSC «BELARUSIAN METALLURGICAL WORKS» - A. D. Korchak; A. I. Rozhkov; I. Yu. Simonyuk (Литьë и металлургия, 2017)
The article describes the results of tests of asbestos-free friction materials in the brake pads cranes at scrap yard of OJSC «BSW». The tests were made on cranes of two manufacturers: PJSC «Tribo», Ukraine and the Metal-Polymer Research Institute of National Academy of Sciences of Belarus. The following aspects were defined: requirements for materials, main features of operation; there were shown the characteristic types of wear in materials.